Comparison of the Punitive Damage with Compensatory, Symbolic, Indirect and Aggravated Damages (Global Journal of Human-Social Science, 2012)
The punitive damage is a kind of damage that should be compensated by the defendant for his her conduct in applying damage tinted with insolence and malice to the plaintiff The origin of this law institution was in Common Law especially in England which has been developed in other countries quickly Some conditions should be provided for demanding the punitive damage The conduct specified in the verdict of punitive damage is the behavior tinted with insolence committed by the defendant on the other hand occurrence of loss is one of the conditions required for demanding the compensation of punitive damage while in other kinds of damages the required conditions for claiming the indemnity are different
Keywords: Punitive damage; compensatory damage; symbolic damage; indirect damage; aggravated damage